Measuring Individual Differences in Driver Inattention: Further Validation of the Attention-Related Driving Errors Scale - Ledesma, Ruben Daniel (2015)
Objective: The aim of this research was (a) to study driver inattention as a trait-like variable and (b) to provide new evidence of validity for the Attention-Related Driving Errors Scale (ARDES). Background: Driving inattention is approached from an individual differences perspective. We are interested in how drivers vary in their propensity to experience failures of attention and in the methods to measure these differences. Method: In a first sample (n = 301), we tested, via confirmatory factor analysis, a new theoretical model for the ARDES. In a second sample (n = 201), we evaluated the relationship between inattention and internal and external sources of distraction and social desirability bias in ARDES responses. A subsample (n = 65) was reevaluated to study temporal stability of the ARDES scores. Results: Errors measured by the ARDES can be classified according to the driving task level at which they occur (navigation, maneuvering, or control). Differences in ARDES scores based on collision history were observed. ARDES was related to internal sources of distraction and was independent of the level of exposure to distracting activities. Test-retest showed a high degree of stability in ARDES scores. Low correlations were found with a social desirability measure. Conclusion: ARDES appears to measure a personal trait that remains relatively stable over time and is relatively independent of distracting activities. New evidence of validity emerged for this self-report. Application: ARDES can be used to measure individual differences in driving inattention and to help tailor preventive interventions for inattentive drivers. It can serve as an instrument of driver self-assessment in educational and training contexts.